Pengaruh Konseling Gizi Daring dan Aktivitas Fisik terhadap Kualitas Diet dan Persen Lemak Tubuh Dewasa Obesitas: The Effects of Tele-Nutrition Counselling and Physical Activity on Diet Quality and Body Fat Percentage in Obese Adults - Prasetyo, Teguh Jati; Wahida, Tresna Putri; Surijati, Katri Andini; Listiandi, Arfin Deri; Sulistyaning, Afina Rachma; Ramadhan, Gumintang Ratna; Khoiriani, Izzati Nur; Wicaksari, Sifa Aulia (Universitas Airlangga, 2026)
Background: Obesity is a global nutrition issue marked by excess body fat and elevated risk of non-communicable diseases. Tele-nutrition counselling has emerged as an alternative strategy to improve dietary behaviour alongside physical activity. Objectives: The study aimed to investigate the effects of tele-nutrition counselling on diet quality and body fat percentage in obese adults. Methods: A quasi-experimental pre-test/post-test control-group design was used with 56 adults selected through purposive sampling, allocated to a control group (exercise) and an intervention group (tele-nutrition counselling + exercise). Both groups received an 8-week physical activity program, while counselling was only given to the intervention group. Diet quality was assessed using a 2×24-hour recall and body fat percentage by BIA OMRON. Data analysis used the Wilcoxon, Paired T-Test, Mann-Whitney, and Independent T-Test. Results: The intervention had an effect on diet quality (p-value=0.038) and body fat percentage (p-value=0.03) in the intervention group. There was no effect on diet quality (p-value=0.556) or percent body fat (p-value=0.448) in the control group. There was a difference in effect on diet quality (p-value=0.038) and no difference in effect on body fat percent (p-value=0.091) in both groups. Conclusions: The intervention affected diet quality and body fat percent in the intervention group but not in the control group. Although the intervention successfully improved diet quality, its impact on body fat percentage was not observed among groups, suggesting that improving eating behaviour needs to be accompanied by other intervention components, such as increased physical activity and a longer program duration.